Experiências formadoras do Centro de Ensino de Línguas da Faculdade de Ciências e Letras de Araraquara - Marques, Sandra Mari Kaneko [UNESP]; Rozenfeld, Cibele Cecílio de Faria [UNESP]; Nadin, Odair Luiz da Silva [UNESP]; Rocha, Nildicea Aparecida [UNESP]; Salomão, Ana Cristina Biondo [UNESP]; Gileno, Rosangela Sanches [UNESP]; Margorari, Denise Maria [UNESP]; Sandes, Egisvanda Isys de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this paper, we aim to present the structure of the extension project entitled “Implementation of the Language Teaching Center FCLAr”. In addition to this, we will briefly describe actions and activities of student-teachers, supervisors and coordinators linked to our Center in the triad Teaching, Research and Extension. Among the key findings and partial assessments, we consider that the project has contributed to the professional and academic background of our student-teachers, since they have the opportunity to: relate language teaching and learning theory to classroom practices; participate in research groups; conduct theoretical and practical research about language teaching and learning at various levels. Furthermore, the Center has been involved in a series of initiatives that seek to promote cultural integration and support to UNESP’s internationalization actions.

Neste trabalho, buscamos apresentar a estrutura do projeto de extensão “Implementação do Centro de Ensino de Línguas da FCLAr”. Além disso, faremos uma breve descrição das ações e atividades de alunos-bolsistas, professoressupervisores e coordenadores vinculadas ao Centro no âmbito da tríade Ensino, Pesquisa e Extensão. Dentre as principais conclusões e avaliações parciais do projeto, consideramos que o Centro vem contribuindo para a formação profissional e acadêmica do aluno-bolsista, uma vez que ele tem a oportunidade de: relacionar teorias acerca do processo de ensino e aprendizagem de línguas à prática em sala de aula; participar de grupos de pesquisa; realizar pesquisas de cunho teórico-prático em diversos níveis. Além disso, o Centro vem se envolvendo em uma série de iniciativas que procuram promover a integração cultural e apoiar as ações de internacionalização da UNESP.
Keywords: Teaching and learning; Foreign languages; Professional education; Ensino e aprendizagem; Línguas estrangeiras; Formação profissional